2009
DOI: 10.1242/dev.028415
|View full text |Cite
|
Sign up to set email alerts
|

Foxa2 regulates polarity and epithelialization in the endoderm germ layer of the mouse embryo

Abstract: In the mouse, one of the earliest events in the determination of cell fate is the segregation of cells into germ layers during gastrulation; however, the cellular and molecular details are not well defined due to intrauterine development. We were able to visualize a clear sequence of events occurring in the process of germ-layer formation, using immunohistochemistry and time-lapse confocal imaging. The T-box transcription factor brachyury (T) and the Forkhead transcription factor Foxa2 specify mesoderm and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
205
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(223 citation statements)
references
References 58 publications
15
205
0
3
Order By: Relevance
“…Whole mount in situ hybridisation and immunohistochemistry were performed according to standard procedures (Burtscher and Lickert, 2009;Chazaud et al, 2006;Perea-Gomez et al, 2004). For histological analysis, embryos were embedded in paraffin and sectioned at 4 µm.…”
Section: In Situ Hybridisation and Immunohistochemistrymentioning
confidence: 99%
“…Whole mount in situ hybridisation and immunohistochemistry were performed according to standard procedures (Burtscher and Lickert, 2009;Chazaud et al, 2006;Perea-Gomez et al, 2004). For histological analysis, embryos were embedded in paraffin and sectioned at 4 µm.…”
Section: In Situ Hybridisation and Immunohistochemistrymentioning
confidence: 99%
“…2b,f) indicates defective development of posterior and proximal epiblast derivatives. Third, an anatomical node (anterior PS derivative), which at E7.5-7.75 constitutes a bilayered structure at the distal tip of the embryo 13,14 (Fig. 2a), was never observed in the mutants (n ¼ 2; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Upon lineage-specific removal of b-catenin, mesoderm-like cells are present in the endoderm layer of mutant embryos suggesting a transfating of endoderm to mesoderm [47], and deletion of b-catenin specifically in Sox17-expressing cells prevents endoderm formation [48]. Nonetheless, based on marker expression, it has been suggested that DE and mesoderm cell lineages might already be predetermined before gastrulation [49], though it should be noted that markers indicate the state, not fate, of cells. If a mesendodermal state indeed exists within the mouse embryo, it is worth considering how it might tie in with a dispersal model of endoderm morphogenesis.…”
Section: (B) Migration Of Definitive Endoderm Progenitorsmentioning
confidence: 99%